2022
DOI: 10.3390/su142114021
|View full text |Cite
|
Sign up to set email alerts
|

Influence Mechanism of Urban Staggered Shared Parking Policy on Behavioral Intentions of Users and Providers Based on Extended Planned Behavior Theory

Abstract: Shared parking has been widely accepted as an effective way to deal with the mismatch between parking demand and supply. Especially for adjacent construction areas with mixed residential and commercial land, staggered shared parking has broad application prospects. From the previous practice, the public welfare from the government, the commercial interests of parking enterprises, and the individual income of residents will be the key elements to promote a staggered parking policy in adjacent construction areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…To capture the intricate relationships between factors and parking intentions, researchers have utilized various data collection and analytical methods, including questionnaires, surveys, interviews, observational studies, choice experiments, revealed preference studies, and agent-based simulations [9,12,14,15,45,46]. Statistical analyses, such as regression models, SEM, and cluster analyses, have been employed to determine the associations between these factors and parking intentions [18,47,48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To capture the intricate relationships between factors and parking intentions, researchers have utilized various data collection and analytical methods, including questionnaires, surveys, interviews, observational studies, choice experiments, revealed preference studies, and agent-based simulations [9,12,14,15,45,46]. Statistical analyses, such as regression models, SEM, and cluster analyses, have been employed to determine the associations between these factors and parking intentions [18,47,48].…”
Section: Literature Reviewmentioning
confidence: 99%